Incisional Hernia After Midline Versus Transverse Specimen Extraction Incision: A Randomized Trial in Patients Undergoing Laparoscopic Colectomy. Issue 1 (July 2018) - Lee, Lawrence; Mata, Juan; Droeser, Raoul A.; Kaneva, Pepa; Liberman, Sender; Charlebois, Patrick; Stein, Barry; Fried, Gerald M.; Feldman, Liane S.
Abstract : Objective: To compare the incidence of incisional hernia (IH) between midline and transverse specimen extraction site in patients undergoing laparoscopic colectomy. Background: Midline specimen extraction incision is most commonly used in laparoscopic colectomy, but has high IH risk. IH may be lower for transverse incision. Methods: A single-center superiority trial was conducted. Eligible patients undergoing laparoscopic colectomy were randomly assigned to midline or transverse specimen extraction. Primary outcome was IH incidence at 1 year. Power calculation required 76 patients per group to detect a reduction in IH from 20% to 5%. Secondary outcomes included perioperative outcomes, pain scores, health-related quality of life (SF-36), and cosmesis (Body Image Questionnaire). Results: A total of 165 patients were randomly assigned to transverse (n = 79) or midline (n = 86) specimen extraction site, of which 141 completed 1-year follow-up (68 transverse, 73 midline). Patient, tumor, surgical data, and perioperative morbidity were similar. Pain scores were similar on each postoperative day. On intention-to-treat analysis, there was no difference in the incidence of IH at 1 year (transverse 2% vs midline 8%, P = 0.065) or after mean 30.3 month (standard deviation 9.4) follow-up (6% vs 14%, P = 0.121). On per-protocol analysis there were more IH after midline incision with longer follow-up (15% vs 2%, P = 0.013). On intention-to-treat analysis, SF-36 domains body pain and social functioning were improved after transverse incision. Cosmesis was higher after midline incision on per-protocol analysis, but without affecting body image. Conclusions: Per-protocol analysis of this trial demonstrates that a transverse specimen extraction site has a lower incidence of IH compared to midline with longer follow-up but has worse cosmesis. Abstract : Supplemental Digital Content is available in the text